HAMBATAN PENERAPAN KURIKULUM ISLAM WASATHIYAH TERHADAP MUATAN PENDIDIKAN MODERATISME PADA MATA PELAJARAN AKIDAH AKHLAK MAS TARBIYAH ISLAMIYAH KEC. HAMPARAN PERAK, KABUPATEN DELI SERDANG - Ependi, Rustam; Rangkuti, Charles; Ismaraidha, Ismaraidha (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
Religious education is one of the important issues because religious education provided in schools does not turn on good multicultural education, even tends to be opposite. As a result, social conflict is often amplified by the religious legitimacy taught in religious education in conflict-prone schools. This makes conflicts that have their roots in fundamental religious beliefs so that social conflicts and violence are increasingly difficult to overcome, because they are understood as their religious vocation. The root of various social conflicts that lead to prolonged anarchy is often problems that have nothing to do with religion, but in reality religion has always been an inseparable part of these social conflicts. The potential for conflict and disintegration is caused because religion in its manifestations is ambivalent towards unity and unity. That is, although religion has the power to unify, religion also has divisive power.